Seaweed (Eucheuma cottonii) Cultivation Business Development Strategy in Tihi-Tihi Village, Bontang Lestari Village, Bontang Selatan District, Bontang City - Lesmana, Ade Resa; Abdusysyahid, Said; Fahrizal, Wahyu (Nusantara Tropical Fisheries Science (Ilmu Perikanan Tropis Nusantara), 2023)
The purpose of this research is to analyze strengths, weaknesses, opportunities, threats and formulate appropriate strategies in developing seaweed cultivation businesses in Tihi-Tihi Village. Strategy formulation using development strategy analysis consisting of SWOT and QSPM analysis. According to the result, the priority strategy recommended for the development of seaweed cultivation is to increase production yields and expand cooperative relationships with buyers who will take the seaweed produced.